Correlation of lipids and lipoprotein concentration with body mass index in obese, overweight and normal weight south Indian adults - B., Gayathri; V. M., Vinodhini (International Journal of Research in Medical Sciences, 2017)
Background: Obesity a chronic disorder is gradually becoming a serious public health problem in many countries. The aim of the study was designed to measure serum lipids and lipoproteins as marker for cardiovascular disease among obese and overweight South Indian adults. Methods: The study was done between June 2016 to December 2016, in SRM medical college hospital and research centre, Kattankulathur which comprised of 270 participants of both gender in the age of 18- 55 years. 90 individuals with body mass index (BMI ≥25kg/m2), 90 individuals with BMI in the range of 23.0 to 24.99kg/m2 and 90 age and sex matched controls (BMI = 18 to 22.99kg/m2) were selected for the study. Serum levels of total cholesterol, Triacylglycerol, high density lipoprotein (HDL-C) and low-density lipoprotein (LDL-C) were analyzed by using auto analyzer Beckman Coulter AU480. The cardiac risk ratio 1 (cholesterol/HDL-C ratio) and 2 (LDL-C/HDL-C) ratio were calculated. Results: The difference between the mean values of total cholesterol, triglycerides and LDL-C, were found to be statistically significant across the three groups. Positive correlation was observed between BMI and cardiac risk ratios one and two in both obese and overweight groups. Conclusions: Cardiac risk is increased in South Indian overweight and obese individuals which is evident from the elevated levels of total cholesterol, triglycerides, LDL-C and cardiac rick ratio one (cholesterol/HDL-C ratio) and two (LDL-C/HDL-C).